Imperatives of development of environmentally clean technology in mechanical engineering - Orlova, Е. (Харківський національний автомобільно-дорожній університет, 2023)
The work is devoted to the actual problem: Increasing the durability of piston rings using a modern method of surface treatment. Solving this problem with the help of traditional methods of chemical and thermal treatment does not give stable industrial results, therefore, the development of the technology of using modern methods and the methodology of their testing is an important urgent task. For the first time in production conditions, a device was created that allows determining the influence of surface treatment methods on wear resistance, crack resistance and structural changes of bearing liners. To perform the work, methods of metallographic X-ray structural, electron microscopic analysis, and modern methods of hardness determination were used. The work describes the development and analysis of the applied coating by the method of two-wire metallization with a steel-molybdenum coating. The coating components - molybdenum and stainless steel (as well as the original materials themselves) have high corrosion resistance, which is not inferior to the corrosion resistance of chrome and cast iron, from which the rings are made.
Імперативи розвитку екологічно чистих технологій у машинобудуванні
Keywords: piston; steel; durability; structure; molybdenum; corrosion; 629.693